COVID vaccine related lower limb gangrene: the first case report - Lal, Nishant; Khan, Saajid Ali; Pillai, Aiswarya R.; Khan, Shafy Ali (International Surgery Journal, 2021)
Though there have been multiple cases of arterial thrombosis and gangrene of limbs reported following COVID-19 infections, there has not been any case reported following COVID-19 vaccinations. Here we reported a case of acute lower limb ischemia following COVID-19 vaccination in a 32 year male with no co-morbidities. The clinical symptoms and signs related to lower limb ischemia started 2 weeks after COVID-19 vaccination. Despite anticoagulation, thrombo embolectomy and intraluminal catheter guided thrombolysis, patient’s left forefoot became gangrenous and had to be amputated.